Cue-induced smoking urges deplete cigarette smokers' self-control resources - Hagger, Martin; Leaver, E.; Esser, K.; Leung, C.; Te Pas, N.; Keatley, D.; Chan, Derwin; Chatzisarantis, Nikos (Springer, 2013)
Background: Exposure to smoking-related cues leads to increased urge to smoke in regular cigarette smokers and resisting these urges requires considerable self-control. Purpose: Adopting a resource depletion model, two studies tested the hypothesis that resisting smoking urges depletes self-control resources. Methods: Adopting a within-participants randomized cross-over design, participants (study 1, N = 19; study 2, N = 32) were exposed to smoking-related (study 1: smoking images; study 2: cigarette cue-exposure task) and neutral (study 1: neutral images; study 2: drinking-straw task) cues with presentation order randomized. After each cue set, participants completed self-control tasks (study 1: handgrip task; study 2: handgrip and Stroop tasks), performance on which constituted dependent measures of self-control.Results: Self-control task performance was significantly impaired when exposed to smoking-related cues compared to neutral cues. No significant presentation-order effects, or interaction effects between stimulus and presentation order, were found. Conclusions: Findings corroborate our hypothesis that resisting smoking urges depletes cigarette smokers’ self-control resources and suggests that self-control capacity is governed by a limited resource.